Perception of visual advertising in different media: from attention to distraction, persuasion, preference and memory - Jaana Simola (Frontiers Research Topics, 2015)
This Research Topic aims to showcase the state of the art in visual advertising research. Although visual processes are a central component of consumer behavior, they have been largely neglected in models explaining consumer perception of advertising. Rather than being the mere input into the cognitive or affective systems, the visual processes both voluntarily and involuntarily affect the amount and quality of information that is passed into further mental processing. Moreover, advertisements provide a well- designed, rich and stimulating environment to study visual processes in real-life conditions. Consumers encounter thousands of advertisement messages per day. Previous research on visual perception of advertising mostly considers print advertising. However, advertising messages increasingly appear in a variety of formats and in different media. Part of these messages are still conveyed through traditional media, such as newspapers, magazines, television, as well as outdoor and supermarket advertising. In addition, the amount and diversity of visual marketing stimuli is rapidly growing in terms of different advertising formats appearing in online and social media, smartphones and tablets. This challenges the marketing professionals and academics to better understand the impact of marketing on consumers. At the same time, the technical development of the research methods allows better opportunities to investigate advertising perception in different environments. Traditionally, papers investigating the psychological processes underlying advertising perception are published in journals widespread across different disciplines, such as marketing, applied psychology and human computer interaction journals. With this Research Topic, we aim to create a forum in which experts in different fields define the state of the art and future directions of the research on the visual aspects of marketing. We include reviews and original research papers involving both empirical and theoretical studies on visual perception of advertising across different media.